Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.solener.2019.03.026
|View full text |Cite
|
Sign up to set email alerts
|

High performance perovskite sub-module with sputtered SnO2 electron transport layer

Abstract: Hybrid perovskite solar cells (PSC) have gained stupendous achievement in single/tandem solar cell, semitransparent solar cell and flexible devices. Aiming for potential commercialization of perovskite photovoltaic technology, up scalable processing is crucial for all function layers in PSC. Herein we present a study on room temperature magnetron sputtering of tin oxide electron transporting layer (ETL) and apply it in a large area PSC for low cost and continues manufacturing. The SnO2 sputtering targets with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 45 publications
1
50
0
1
Order By: Relevance
“…Notably, m-TiO 2 , currently still the most employed ESL, usually needs high-temperature sintering at ≈500 °C, which is required to eliminate the organics/additives, resulting in the mesoporous structure. [115,116] SnO 2 can also be fabricated in a mesoporous structure through a similar high-temperature annealing step. [117] However, m-SnO 2 -based PSCs have remained less efficient compared to their m-TiO 2 counterparts, for two main reasons.…”
Section: Low-temperature Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, m-TiO 2 , currently still the most employed ESL, usually needs high-temperature sintering at ≈500 °C, which is required to eliminate the organics/additives, resulting in the mesoporous structure. [115,116] SnO 2 can also be fabricated in a mesoporous structure through a similar high-temperature annealing step. [117] However, m-SnO 2 -based PSCs have remained less efficient compared to their m-TiO 2 counterparts, for two main reasons.…”
Section: Low-temperature Processingmentioning
confidence: 99%
“…Following this, Bai et al recently reported sputtered SnO 2 ESLs at room temperature for mini-modules (again with an active area of 22.8 cm 2 ) with a champion PCE of 14.71%. [116] The main challenge for the sputtering method lies in control of oxygen vacancies in the SnO 2 film, which is usually accomplished by tuning the gas flows during processing or postannealing. Another concern is the amorphous or nanocrystalline nature of the films, causing tail states within the bandgap, which may result in V OC losses.…”
Section: Magnetron Sputteringmentioning
confidence: 99%
“…Compared with DC sputtering that uses conductive SnO 2 target, RF sputtering of nonconductive SnO 2 produces ETL that leads to higher performance and is indeed commonly used in most works. [ 91 ] The electron configuration in the outermost occupied shell is the cause of two types of tin‐relate oxide: p‐type SnO with relatively high and tin vacancy–associated hole mobility, and n‐type SnO 2 whose conductivity originates from intrinsic defects like oxygen vacancies and tin interstitial. The latter one is obviously desired for the application as ETL.…”
Section: Etlsmentioning
confidence: 99%
“…Whereas over‐high content leads to undesired interstitial oxygen and rougher morphology. [ 91,93 ] Full coverage of the underlying layer requires thick‐enough SnO 2 film, but the Ar plasma damage and increased charge transport resistance coming with thicker films would cause a loss in FF . Balancing these effects leads to an optimum thickness.…”
Section: Etlsmentioning
confidence: 99%
“…The hybrid organic inorganic lead (Pb) based perovskite as an light absorber (APbI3) is the most investigated in PSCs due to their excellent electro-optical properties [1][2][3][4][5] and gave record performance. 6,7 However, hybrid organic-inorganic lead halide perovskite suffers from challenges such as, efficiency, 8 thermal instability at high temperature, originating due to volatile nature of organic cations (FA or MA). 9,10 Replacement of the organic cations by inorganic cations such as Cs found to be an effective approach to overcome such bottleneck.…”
Section: Introductionmentioning
confidence: 99%